Phrasebook: una salida para los maestros de CLIL en Tailandia - Punwalai Kewara (Universidad de La Sabana, 2017)
Content and Language Integrated Learning (CLIL) is an alternative approach for En- glish teaching and learning that is in focus in Thailand today. Preparing Thai content teachers to con dently use English as a means of instruction in the English integrated classroom just as they do in the Thai monolingual classroom takes time and long-term nancial investment. Creating a classroom language manual for mathematics teachers to promptly use is a way out for those professionals who struggle with language. This article aims to examine the possibility of providing prefabricated classroom language sentences to Thai content teachers who need language support in order to identify the appropriateness of the components of the manual and the language for classroom use, in order to create a motif of language support for other subjects. In addition, this paper aims to explore Thai mathematics teachers' perception toward the CLIL classroom. The phrasebook design was based on a unit of mathematics at the primary level for 25 Thai mathematics teachers to implement in their classes. The results revealed that the designed prefabricated phrasebook could be a way out. Prefabricated phrases should respond to the speci cation of mathematics concepts for each level. Ultimately, the CLIL concept should be clearly established for Thai content teachers to make CLIL classes effective and possible.  doi: 10.5294/laclil.2017.10.1.3